Latin et vernaculaire dans les écritures administratives de la principauté de Savoie: L'exemple des comptes généraux du XIV siècle. - Gaulin, Jean-Louis (Médiévales)
The Principality of Savoy continued to use Latin as its language of administration up until the crisis caused by the French occupation during the years 1536-1559. However, the examination of a series of book accounts compiled by financial officers in the fourteenth century shows that accompanying documents written in vernacular-a middle French with Franco-Provençal features-could, as part of a highly regulated administrative procedure, have had a place in this accounting process. The records of the House of Savoy therefore offer a field of inquiry that is particularly useful for studying the bilingualism of the Prince's officers in their daily work.